Information Security Breaches Avoidance and Treatment based on ISO27001 - Krausz, Michael (IT Governance Pub., 2009)
This pocket guide outlines a process and its elements for the treatment of severe breaches, and places them in the context of the associated ISO27001 controls. Firslty it offers a general discussion of what information security breaches are, and secondly it helps rform a first line of defence for the reader who is the victim of an incident and is looking for guidance and direction.
Includes bibliographical references. - Print version record
Keywords: Business enterprises -- Computer networks -- Security measures; Computer security -- Management -- Standards; Data protection -- Management -- Standards; Sécurité informatique; Gestion; Normes; Protection de l'information (Informatique); Gestion; Normes; COMPUTERS; Internet; Security; COMPUTERS; Networking; Security; COMPUTERS; Security; General; Business enterprises; Computer networks; Security measures